Density functional investigations of electronics structure and dehydrogenation reactions of Al- and Si-substituted magnesium hydride - Kelkar, Tuhina; Pal, Sourav; Kanhere, Dilip G. (ChemPhysChem, 2008)
{The effect on the hydrogen storage attributes of magnesium hydride (MgH2) of the substitution of Mg by varying fractions of Al and Si is investigated by an ab initio plane-wave pseuodopotential method based on density functional theory. Three supercells, namely, 2 x 2 x x 3 x 1 x 1 and 5 x 1 x 1 are used for generating configurations with varying amounts (fractions x=0.0625, 0.1, and 0.167) of impurities. The analyses of band structure and density of states (DOS) show that, when a Mg atom is replaced by Al, the band gap vanishes as the extra electron occupies the conduction band minimum. In the case of Si-substitution, additional states are generated within the band gap of pure MgH2-significontly reducing the gap in the process. The reduced band gaps cause the Mg-H bond to become more susceptible to dissociation. For all the fractions, the calculated reaction energies for the stepwise removal of H-2 molecules from Al- and Si-substituted MgH2 ore much lower than for H-2 removal from pure MgH2. The reduced stability is also reflected in the comparatively smaller heats of formation (Delta H-f) of the substituted MgH2 systems. Si causes greater destabilization of MgH2 than Al for each x. For fractions x = 0.167 of Al
Keywords: band structure; Density functional calculations; hydrides; Hydrogen storage; Thermodynamics

First principles calculations of thermal, equations of state and thermodynamical properties of MgH2 at finite temperatures - Kelkar, Tuhina; Kanhere, Dilip G.; Pal, Sourav (Computational Materials Science, 2008)
We present the first principles calculations of the thermodynamical properties of magnesium hydride (MgH2) over a temperature range of 0-1000 K. The phonon dispersions are determined within the density functional framework and are used to calculate the free energy of MgH2 within the quasiharmonic approximation (QHA) at each cell volume and temperature T. Using the free energies the thermal equation of state (EOS) is derived at several temperatures. From the thermal EOS structural parameters such as the equilibrium bell volume (V-0) and elastic properties, namely, bulk modulus (K-0) and its pressure derivative (K-0(')) are computed. The free energies are also used to calculate various thermodynamical properties within QHA. These include internal energy E, entropy S, specific heat capacity at constant pressure C-P, thermal pressure P-thermal(V,T) and volume thermal expansion Delta V/V (%). The good agreement of calculated values of S and Cp with experimental data exhibits that QHA can be used as a tool for calculating the thermodynamical properties of MgH2 over a wide temperature range. P-thermal(V,T) increases strongly with T at all the volumes but it is a slowly varying function of volume for T = 298-500 K. According to Karki [B.B. Karki, Am. Miner. 85 (2000) 1447] such volume based variations can be neglected and so it is possible to estimate the thermal EOS only with the knowledge of the measured P-thermal(V,T) versus temperature at ambient pressure and isothermal compression data at ambient temperature. Temperature dependence of Delta V/V(%) shows that V-0 increased with increase in temperature. However, the percentage decrease in K-0 superseded this percentage increase in V-0 even at temperatures moderately higher than 298 K. Therefore, we suggest application of temperature (T > 298 K) as an approach to enhance the hydrogen storage capacity of MgH2 because of its better compressibility at these temperatures. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: equation of state; Hydrogen storage; lattice dynamics; magnesium hydride; Thermodynamic properties

Computational study of electronic structure, thermodynamics and kinetics of hydrogen desorption from Al- and Si-doped alpha-, gamma-, and beta-MgH2 - Kelkar, Tuhina; Pal, Sourav (Journal of Materials Chemistry, 2009)
First principles calculations of pure and Al-and Si-doped alpha-, gamma-, and beta-MgH2 were performed to investigate the influence of Al and Si as impurities and the presence of high pressure phases on the properties of hydrogen sorption of magnesium hydride. The ab initio plane wave pseudopotential method based on density functional theory within the generalized gradient approximation was used in the present study. The total energies of the considered systems were calculated as a function of cell volume to obtain material properties such as bulk modulus K-0, equilibrium cell volume V-0 and minimum energy E-0(V-0). From the density of states (DOS) analysis, it was shown that doping MgH2 with Al and Si caused a reduction in the band gaps of each of the three phases. The diminished band gaps made the Mg-H bond more susceptible to dissociation. The destabilization of the hydrides was reflected in the decreased heats of formation of the doped hydrides, with the following Delta H-f order: Si < Al and beta < gamma < alpha. A 30.5% reduction in the activation energy barrier E-act for H-2 desorption was calculated for the Al-doped alpha-MgH2(001) surface and a 15.5% decrease in E-act of the Si-doped gamma-MgH2(001) surface was deduced, while doping with Al and Si increased the activation energy barrier for the beta-MgH2 (001) surface drastically.